Seedlings Performance of Triplochiton scleroxylon (K. Schum.) under Different Light Intensities and Soil Textural Classes - O. A, Iroko; I.O, Asinwa; M.A, Odewale; W.T, Wahab (Journal of Forests, 2020)
Forest trees are socio-economically important but are currently threatened. This study adopted 4×4 factorial experiment in completely randomized design with ten replicates to assess effects of light intensities (100%LI, 75%LI, 50%LI and 25%LI) and soil textural classes (Sandy, Loamy, Sandy-loam and Clay) on the early growth of Triplochiton scleroxylon seedlings as a necessary step for domestication. Data collected was subjected to One-way Analysis of Variance (ANOVA). The best performance for light intensity was observed under 100%LI with plant height 14.79±1.26cm, collar diameter 2.28±0.18mm and 13.11±0.96 number of leaves while the least performance was observed in seedlings under 25%LI with seedling height 10.23±0.59cm, collar diameter 1.97±0.13mm and 6.41±0.45 number of leaves and best performance in soil textural classes was recorded under loamy soil with seedling height 14.90±1.20cm, collar diameter 2.33±0.18mm and 13.11±0.32 number of leaves while the least performance was observed in seedlings grown with sandy soil with seedling height 11.00±0.61cm, collar diameter 1.99±0.13mm and least number of leaves was recorded in seedlings with sandy-loam with 7.41±0.55 number of leaves. Overall best performance was observed in seedlings grown with sandy-loam under 100%LI with seedling height 23.80±0.75cm, collar diameter 4.69±0.34mm and 14.79±0.29 number of leaves while the least performance was observed in seedlings grown with clay under 25%LI with seedling height 10.30±0.68cm, least collar diameter 3.69±0.28mm and number of leaves 13.69±0.28 was observed in seedlings grown with sandy soil under 75%LI. Therefore, it implies that the specie require little or no shade for rapid growth and will thrive well with sandy-loam soil.